An estimation of direction of reorganization of the system of local self-government is in Kazakhstan (Вестник КазНУ. Серия Экономическая, 2016)
Possibilities are created for appearance at local level of new elite, that will be able to master democratic skills and functions, necessary for par ticipating in political life of country.Decentralization assists the increase of receptivity of government bod ies to the local necessities and problems. When responsibility for the grant of services and providing of infrastructure is decentralized, local organs can better estimate correlation of charges and acuestss, and also more flexibly to react on the necessities of population within the framework of budget constraints